Meningkatkan Keterampilan Anggota Berdasarkan Kemanusiaan, Teknologi, dan Pendidikan - Muhlisin; Hidayatullah, Syarif; Balbisi, Dina Nur Amilah (Presisi Jurnal Pengabdian Masyarakat, 2023)
UKK KSR PMI IAIN Pekalongan Unit is a Special Activity Unit at IAIN Pekalongan tertiary institutions which is based on PMI Pekalongan City. Education and training for KSR members in addition to producing members who are qualified in the field of red cross and other supporting knowledge.  An organization requires regeneration, restructuring and also the dissemination of knowledge or skills possessed by the previous generation to the generations below. To produce competent members, one of the supporting work programs is education of volunteers.  In the education of volunteers, there are three types of training, namely planning learning devices, introduction of facilitators and fieldwork. Each of the three trainings has its own division. The method used is the ABCD method. ABCD method or Asset Based Communities Development (ABCD) is a model approach in community development. The results obtained are that the education of volunteers can increase the knowledge of the volunteers, improve the skills of members and build camaraderie and build chemistry between division members. Keywords: education, volunteers, red cross. ,